(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was accomplished to assess the comparativeperformance of the dry, semi-dry and soft date palm types under theconditions of the Northern State, Sudan. Four date representativecultivars, grown in Elghaba Agricultural Scheme, were compared;.theirage ranged between 30 and 34 years. The cultivars were Barakawi andGondaila (dry), Wadkhteeb (semi-dry) and Madina (soft). Data recordedfor vegetative growth parameters were stem circumference, leaf numberand length, number of pinnae/leaf, length of pinnae, number of thorns/leafand width of leaf base. Data were also collected for number of bunches,bunch weight and yield/palm. The results indicated significant differencesbetween the four cultivars. Wadkhteeb excelled the other cultivars innumber of leaves, bunch weight and yield/palm, without being affected bythe phenomenon of alternate bearing. The superiority of Wadkhteeb inyield is indicative of the suitability of the semi-dry cultivars to theconditions of the Northern State.